IMPLEMENTING MUTUAL LEGAL ASSISTANCE (MLA) IN MONEY LAUNDERING: A CASE OF PT. CIPTA GRAHA NUSANTARA - Azzuhra, Fazila; Haflisyah, Teuku; Rahmah, Siti (Universitas Syiah Kuala, 2024)
This article clarifies the laws and regulations governing the implementation of mutual cooperation in cases of money laundering linked to corruption. It specifically examines the application of MLA in the context of PT Cipta Graha Nusantara. Using a normative legal research methodology, this study analyzes international treaties and domestic legislation, focusing on their application within the judicial process. Data collection involved document analysis of relevant domestic and foreign regulations. The findings indicate that Indonesia and Switzerland have ratified a mutual assistance agreement in criminal matters (Law No. 5 of 2020) and that Law No. 1 of 2006, concerning Mutual Legal Assistance in Criminal Matters, has also been ratified. It is the responsibility of the Indonesian government to facilitate the prosecution of its citizens involved in transnational crimes. It is recommended that the government enhance collaboration with other countries facing similar legal issues to streamline the legal processes for tackling transnational crimes. Additionally, effective coordination among relevant ministries and institutions is crucial for facilitating MLA procedures.